2001
DOI: 10.1002/1521-4079(200110)36:8/10<749::aid-crat749>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impurities on the Growth Kinetics of Crystals

Abstract: This paper reviews the work made by the group of the present author on the effect of impurities on the kinetics of crystal growth in solutions. The impurity effect is here discussed in the light of the model proposed by Kubota and Mullin [J. Crystal Growth, 152 (1995) 86], in which impurities are assumed to be adsorbed on the step lines at kink sites following the Langmuir mechanisms for inhibition of step displacement with a modified pinning mechanism. Effects of impurity concentration and supersaturation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 21 publications
7
156
0
1
Order By: Relevance
“…De Villeneuve et al (2005) reported that impurities could influence the nucleation, growth, and structure of crystals. Kubota (2001) also addressed that crystal growth is markedly affected by the impurities presented in the system. Our observational results are also in agreement with our previous study .…”
Section: Characteristics Of Cu-doped Tio 2 Nanoparticlesmentioning
confidence: 99%
“…De Villeneuve et al (2005) reported that impurities could influence the nucleation, growth, and structure of crystals. Kubota (2001) also addressed that crystal growth is markedly affected by the impurities presented in the system. Our observational results are also in agreement with our previous study .…”
Section: Characteristics Of Cu-doped Tio 2 Nanoparticlesmentioning
confidence: 99%
“…Тем не менее на гранях бипирамиды двумерные заро-дыши образуются также при пересыщении ниже крити-ческого, но их распространение невозможно, поскольку здесь критический размер зародыша больше, чем рас-стояние между прочно адсорбированными примесями -так называемыми стопорами Кабреры и Вермили [9] или Куботы и Маллина [10]. В [9] рассматривается образование стопоров на террасах, а в [10] -на сту-пенях.…”
Section: отсутствие роста и адсорбция примесиunclassified
“…[120][121] The additives are usually adsorbed onto specific crystal faces in a certain way that disrupts their continuous growth, and as a result these crystals faces grew in size. Morphological changes caused by additives that are similar in structure can be divided into two major cases, the inclusion of a 'disrupter' guest molecule or the inclusion of a 'blocker' guest molecule on the growing host crystal.…”
Section: Chiral Resolution By Crystallization In the Presence Of Solumentioning
confidence: 99%